EFEKTIFITAS PEMANASAN KAMAR ASAP MELALUI DISTRIBUSI UDARA MASUK (FORCED DRIVE FAN/FDF) DAN UDARA KELUAR (INDUCED DRIVE FAN/IDF) PADA PENGOLAHAN KARET LEMBARAN (RIBBED SMOKE SHEET) : REVIEW - Faisal, Busrizal; Effendi, Zulham (Institut Teknologi Sawit Indonesia (ITSI), 2023)
The smoke chamber used has a capacity of 3,420 kg with a rubber sheet smoking period of five days. Reducing the water content (moisture content) on the rubber sheet is used by heating it with a smoking system. For smoke chamber operations, the fumigation temperature used on the first day is 40 - 45°C, on the second day 45 - 50°C, on the third day 50 - 55°C, on the fourth day 55 - 60°C, and on the fifth day the smoking temperature was maintained at 60°C. FDF and IDF are two air distribution devices, where the FDF functions to blow the air into the smoke chamber and the IDF draws the air into the smoke chamber. The balance between exhaled air and that drawn out of the smoke chamber must be proportional. Too much airflow will collect in the smoke chamber and too much the air withdrawal will affect heat transfer. After installing the FDF and IDF tools, the smoking time is 4 (four) days, so the use of smoked wood (rubber stem wood) is reduced from 3.19 m3 (for 5 days of smoking) to 2.55 m3 (for 4 days of smoking). There is a saving of one operational day. Reducing the use of smoked wood has an impact on processing efficiency. Heat energy from smoking has also increased. Before the installation of the FDF and IDF devices, the amount of heat energy was 64,074 kcal/day (320,372 kcal in 5 days). After installing the FDF and IDF devices, they increase the amount of air / oxygen (O2) in the combustion process so that there is an additional heat energy of 9,461 kcal/day (47,305 kcal in 5 days). The total amount of heat energy produced is 367,677 kcal for 5 (five) days of smoking. FDF and IDF are two air blowers commonly known as blowers with their respective specifications: The FDF used has an electric power of 3 kilowatts (4 horsepower/hp) with a rotation of 1,420 rpm, while the IDF has an electric power of 7.5 kilowatts (10 horsepower/hp). hp) at 1,440 rpm.